Novel mesoporous microspheres of Al and Ni doped LMO spinels and their performance as cathodes in secondary lithium ion batteries. Issue 7 (28th May 2017) - Mukherjee, Santanu; Schuppert, Nicholas; Bates, Alex; Lee, Sang C.; Park, Sam
ABSTRACT: A facile, scalable, and solution-based technique is used to fabricate Al and Ni-doped (LiAl0.1 Mn1.9 O4 and LiAl0.1 Ni0.1 Mn1.8 O4 ) microspheres of lithium manganese oxide (LMO) spinels for use as reversible cathode materials for lithium ion batteries (LIBs). The spheres of the two samples exhibit different porosities. Cells with these LMO-based cathodes are then cycled between 4.5 V and 2 V to study their stabilities while simultaneously being subjected to the undesirable Jahn-Teller distortion that occurs around the 3 V regime. The LiAl0.1 Mn1.9 O4 (LAMO) and the LiAl0.1 Ni0.1 Mn1.8 O4 (LANMO) cells exhibit comparable open circuit voltages (OCV) of 2.94 V and 2.97 V, respectively. During cell cycling, the LAMO cell exhibits a maximum specific capacity of 122.51 mAh g −1 with a capacity fade of 65.35% after 75 cycles. The LiAl0.1 Ni0.1 Mn1.8 O4 (LAMO) sample fares better and exhibits a maximum of 140.49 mAh g −1 and a capacity drop of 52.59%. Detailed structural studies indicate that Ni doping and the greater degree of porosity of the LANMO sample to be a stabilizing factor. This is further confirmed by cyclic voltammetry (CV) and AC impedance spectra analysis.